The Effect of Using Moodle Reader as an Extensive Reading Tool on Learners’ Awareness of Affective Dimensions of Deep Vocabulary Knowledge - Vaezi, Ramin; Nilforooshan, Somayeh (Richtmann Publishing, 2013)
This study aimed at investigating the effect of using MoodleReader to promote extensive reading (ER) in an Iranian EFLcontext, emphasizing its effect on learners' awareness of two affective dimensions namely evaluation and potency of deepvocabulary knowledge. Sixty intermediate EFL female adult learners participated in this study; they were chosen from among90 students through Preliminary English Test and a general vocabulary knowledge test. They were thus randomly divided intotwo groups, experimental and control, each consisting of 30 students. As for the treatment, the experimental group used theMoodleReader for their extensive reading program, while the control group followed the conventional extensive readingcurriculum, reading a small number of pre-assigned graded readers during the semester. At the end, students took a test ofawareness of evaluation and potency dimensions of deep vocabulary knowledge. To see if using MoodleReader hadstatistically significant effects on awareness of evaluation and potency dimensions of deep vocabulary knowledge, independentT-test with 0.05 significant level was administered revealing that using MoodleReader as an extensive reading tool significantlyimproved learners’ awareness of the two dimensions.